Capsule development, in vitro germination and plantlet acclimatization in Phragmipedium humboldtii, P. longifolium and P. pearcei - Muñoz, Melania (Universidad de Costa Rica, 2008)
Capsule development from pollination to full ripeness was evaluated in Phragmipedium longifolium, P. pearcei and P. humboldtii. Besides, seed viability, analyzed in each capsule by means of the tetrazolium chloride staining, was determined. Considering seed viability, germination rate was corrected and expressed as the rate of viable seeds that germinated in the presence and absence of light, on Knudson C and on half-strength Murashige and Skoog culture media. Capsule length remained constant during the evaluation period, while the diameter increased during the first 6-8 weeks and then stagnated. Capsule opening occurred 16 weeks after pollination in P. longifolium, after 9.8 weeks in P. pearcei and after 32 weeks in P. humboldtii. Seed viability averaged 44.7% in P. longifolium, 82.3% in P. pearcei and 34.3% in P. humboldtii. No significant effect of light conditions was evident in any of the species. However, a higher proportion of seeds of P. longifolium and P. pearcei germinated earlier on half-strength Murashige and Skoog medium than on Knudson C. Only 2.9% of the viable seeds of P. humboldtii germinated, while approximately 40% germination occurred in the other two species. Initial growth of the embryos was better in the dark on Knudson C medium, compared to the other treatments studied. Further growth of the seedlings took place under light conditions. Developed plants formed roots and were successfully acclimatized in the greenhouse.